The impact of burnouts on performance and well-being among first year international students - Sarkisian, Angelina (2023)
The object of the paper is to describe and get acquainted with the problem of burnout and find the "triggers" of such emotional state using a questionnaire and sample methods among participants -the young generation, to be exact- first-year students who just graduated from high school and have not yet gotten any feelings that they have achieved something in their lives, confused because of the uncertain future and who may feel frustrated due to the thought that their lives are meaningful. They do not yet have some stability in their lives, even though they have just graduated high school. There are an analysis of different articles and discussion of differences between stress and burnout. This thesis further answers hypotheses, based on quantitative analysis, which has shown that students are affected by personal burnout, self-doubt, and parents‘ influence. These stressors may be suppressed by creating a supportive environment and healthy lifestyle. The thesis has a high value due to its uniqueness, no other work was conducted in Czech Republic, and spreads the information of mental health importance.